Representations of the economic crisis and austerity politics - Novelli, Edoardo; Rafter, Kevin; Alvares, Claudia; Veríssimo, Iolanda; Poulakidakos, Stamatis; Veneti, Anastasia; Triga, Vasiliki; Milioni, Dimitra L.; Sammut, Carmen (My University, 2017)
In the period between the 2009 and 2014 elections to the European Parliament, the international economic recession and related global debt crisis impacted seriously in several European Union (EU) member states. The rights and wrongs of debt fuelled growth and bank bailouts packages shaped political discourse not just in member states seeking sovereign external support but also placed great strain on the European project and raised real questions about the very future of the eurozone. The discussion draws on the content analysis data set generated from the assessment of posters and videos in the 2014 European Parliament election. The subsample in this chapter – focused on countries which experienced significant economic decline due to the post-2008 crisis – includes 321 items – 188 posters and 133 videos – which enables significant comparisons of trends and differences in six member states (Ireland, Greece, Portugal, Cyprus, Italy and Malta). Moving beyond this core group of countries, in the final section of the chapter we examine how themes such as ‘austerity’ were also evident in other member states and discuss how the economic backdrop to 2014 elections was evident in posters and broadcast spots produced by parties and candidates across the EU. It is possible to conclude that the ideological issues and national themes that played in the past an important role (Reif and Schmitt 1980) have been replaced by economic issues. The conomy and the crisis have become the new battlegrounds among parties, even bypassing the traditional distinction between right and left. The 2014 European Parliament campaign allows us to talk of the existence of a European anti-European campaign, which may well be a feature of EU politics beyond the economic crisis itself.
Keywords: Posters; Videos; European Parliament; Election